A semantic annotation for MaaS services: the SA4MaaS approach. (2016) - Midouni, Sid Ahmed Djallal; Amghar, Youssef; Chikh, Azeddine
In a previous work, we have defined a full service approach to compose MaaS services for multimedia data researching. This approach is based on a four-phase process: description, filtering, clustering and restitution. In this work, we are especially interested in the description phase of multimedia web services. Several approaches have been defined with the aim to semantically describe web services. We propose a new approach, Semantic Annotation for MaaS (SA4MaaS) services, as an extension of the W3C recommendation on semantics for web services (SAWSDL). We use two ontologies: a Domain Ontology, whose concepts define semantics of the business domain, and a Multimedia Ontology, whose concepts define a set of annotation properties for describing multimedia content. We show via our implementation how to automatically generate SAWSDL files from SA4MaaS annotations. An evaluation in a medical domain is allowed to validate the approach.